Design, synthesis and biological assessment of N-adamantyl, substituted adamantyl and noradamantyl phthalimidines for nitrite, TNF-α and angiogenesis inhibitory activities. Issue 8 (1st May 2018) - Luo, Weiming; Tweedie, David; Beedie, Shaunna L.; Vargesson, Neil; Figg, William D.; Greig, Nigel H.; Scerba, Michael T.
Graphical abstract: Abstract: A library of 15 novel and heretofore uncharacterized adamantyl and noradamantyl phthalimidines was synthesized and evaluated for neuroprotective and anti-angiogenic properties. Phthalimidine treatment in LPS-challenged cells effected reductions in levels of secreted TNF-α and nitrite relative to basal amounts. The primary SAR suggests nitration of adamantyl phthalimidines has marginal effect on TNF-α activity but promotes anti-nitrite activity; thioamide congeners retain anti-nitrite activity but are less effective reducing TNF-α. Site-specific nitration and thioamidation provided phthalimidine 24, effecting an 88.5% drop in nitrite concurrent with only a 4% drop in TNF-α. Notable anti-angiogenesis activity was observed for 20, 21 and 22 .